Collective interactions among organometallics are exotic bonds hidden on lab shelves - Shahin Sowlati-Hashjin; Vojtěch Šadek; SeyedAbdolreza Sadjadi; Mikko Karttunen; Angel Martín-Pendás; Cina Foroutan-Nejad (Nature Communications)
Abstract Recent discovery of an unusual bond between Na and B in NaBH3 − motivated us to look for potentially similar bonds, which remained unnoticed among systems isoelectronic with NaBH3 −. Here, we report a novel family of collective interactions and a measure called exchange-correlation interaction collectivity index (ICIXC; $${ICI}\in \left[{{{{\mathrm{0,1}}}}}\right]$$ I C I ∈ 0, 1 ) to characterize the extent of collective versus pairwise bonding. Unlike conventional bonds in which ICIXC remains close to one, in collective interactions ICIXC may approach zero. We show that collective interactions are commonplace among widely used organometallics, as well as among boron and aluminum complexes with the general formula [Ma+AR3]b− (A: C, B or Al). In these species, the metal atom interacts more efficiently with the substituents (R) on the central atoms than the central atoms (A) upon forming efficient collective interactions. Furthermore, collective interactions were also found among fluorine atoms of XFn systems (X: B or C). Some of organolithium and organomagnesium species have the lowest ICIXC among the more than 100 studied systems revealing the fact that collective interactions are rather a rule than an exception among organometallic species.